Satisfaction with the Police in Chile: The Importance of Legitimacy and Fair Treatment - Dammert-Guardia, L; Elorrieta-Lopez, F (Cambridge University Press, 2021)
This study addresses a void in the literature on public attitudes toward police in Latin America. It integrates three theoretical models of the determinants of citizen satisfaction with police work in Chile: demographic, quality of life in the neighborhood, and experiential. The study tested the integrated model using a novel random sample of 996 individuals living in the Metropolitan Region of Santiago. The results underscore the importance of legitimacy centered on fair treatment, respect for human rights, and the perception that the police represent society. The findings are also significant for the Chilean institutional political process and for the Latin American police reform debate. © 2021 Cambridge University Press. All rights reserved.